Breach of Contract in Credit Agreements Secured by Land Rights at PT BPR Gajah Mungkur - Apriyani, Nada Karima; Asmaniar, Asmaniar; Mutiarany, Mutiarany (Justice Voice, 2024)
This study examines defaults in credit agreements secured by land collateral at PT BPR Gajah Mungkur, with particular emphasis on legal protection mechanisms available to creditors when debtors fail to meet their obligations. Although credit agreements are supported by a strong legal framework, incomplete registration of mortgage rights can undermine the creditor’s legal standing. The objective of this research is to address gaps in existing studies concerning creditor protection in mortgage enforcement and to analyze the implications of the Supreme Court Decision No. 469 K/Pdt/2024 on the practice of credit agreements in Indonesia. A normative juridical approach was employed, utilizing data sources such as court decisions, statutory regulations, and pertinent legal literature on credit agreements. The findings indicate that incomplete or delayed registration of mortgage rights significantly impedes creditors’ ability to execute collateral. The case study of PT BPR Gajah Mungkur demonstrates that, despite the formal validity of credit agreements, failure to register as a preferred creditor adversely affects the creditor’s right to debt repayment. This research contributes to legal theory by reinforcing the critical role of mortgage registration in enhancing creditor protection. Practically, it offers valuable insights for legal practitioners, emphasizing the necessity of properly completing the mortgage registration process to safeguard creditor interests in cases of debtor default.